BIOSORPTION OF CHROMIUM IONS BY CALCIUM ALGINATE NANOPARTICLES - Sadiq, Asma; Choubey, Anita; Bajpai, A. K. (Journal of the Chilean Chemical Society, 2018)
The objectives of the present work include synthesis of nanoparticles of calcium alginate by emulsion crosslinking method, their characterization by techniques such as FTIR, scanning electron microscopy (SEM), XRD, particle size and surface charge analysis, and study of removal of chromium ions from synthetic aqueous solutions. In order to study the effect of various factors like adsorbent dose, initial metal ion concentration, pH and temperature on the adsorption of chromium ions from water, a series of batch sorption experiments were conducted. The obtained results were analysed by Langmuir and Freundlich isotherm models and it was found that the adsorption of chromium more precisely follows Langmuir absorption isotherm. The metal ion removal capacity of the nanoparticles was found to depend on the chemical composition of the adsorbent, concentration of the metal ion solution, pH and temperature of the medium and speed of the suspension from wastewater before disposal.